UJI AKTIVITAS ANTIBAKTERI REBUSAN DAUN SIRIH (Piper betle Linn) TERHADAP BAKTERI Streptococcus pyogenes - nyoman mastra (Meditory : The Journal of Medical Laboratory, 2019)
ABSTRACTBackground: Infection is a disease caused by pathogenic microbes and is very dynamic. ISPA is defined as an acute respiratory disease caused by infectious agents that were transmitted from human to human. One of the microbes that caused ISPA is Streptococcus pyogenes, which is a gram-positive bacteria and belongs to Streptococcus sp. β-hemolytic class A. Nowadays, many people are begin to use natural materials to deal with microbial infections. One of them is the betel leaf (Piper betle Linn.) Which has antibacterial and antibiotic components for the treatment of respiratory problems, and bacterial infectious diseases.Purpose: This research was conducted with the aim to know the antibacterial activity of betel leaves (Piper betle Linn) decoction against Streptococcus pyogenes bacteria. Methods: This research used true experimental design with Posttest Only Control Design, and data analysis with One Way Anova and Least Significant Deference (LSD). Betel leaves decoction water is made in concentrations of 20%, 40%, 60%, 80%, and 100%, then tested on Streptococcus pyogenes bacteria with two replicates and four repetitions.Result: From a total of 40 data obtained, the mean diameter of the inhibitory zone at each concentrations is 20% 0 mm, 40% 12.9 mm, 60% 22.7 mm, 80% 25.5 mm, and 100% 30 mm.Conclution: Betel leaves decoction water is able to inhibit the growth of Streptococcus pyogenes with significant difference of drag zone diameter at each concentration.  Keywords: Antibacterial, Betel Leaves, Streptococcus pyogenes